Touch restriction during small-sided games in soccer - effects on physiological, physical and technical and tactical performance - Rumpf, M. C.; Jäger, J.; Altmann, S.; Lochmann, M. (Frontiers in Sports and Active Living, 2025)
Limited time and space availability during matches forces soccer players to utilize one-touch (1-touch) or two-touch (2-touch) passes to successfully maintain ball possession. Consequently, coaches replicate game demands during training, implementing touch restrictions into small-sided games (SSGs). 1-touch and 2-touch play increases the intensity and the perceived exertion of the SSGs in adult soccer. Physical variables that are associated with greater external load, such as sprinting or high-intensity running increased with touch restriction independent of skill level and player numbers. 1- and 2-touch play increase the players' technical engagement with the game (e.g., number of passes), however, resulting in positive (%successful passes) as well as negative (%unsuccessful passes) outcomes. Very scarce scientific resources exist with regards to tactical changes with touch restrictions in SSGs indicating indifferent results across age groups and limited tactical variables. Depending on the training goal, coaches can apply touch-restrictions to increase or decrease physical, physiological, technical and tactical activity of players.